Paul Ricoeur: o el reconocimiento como experiencia de donación mutua - Rebok, María Gabriela (ARFIL y UNL, 2019)
This article gives an approach, from Ricoeur's perspective, to the relevance of the idea of mutual acknowledgment in the socio-political contemporary philosophy. Thus, Hegel's proposal of this concept and the reception as well as the critical actualisation by Axel Honneth are outlined. Further, we explain that the peculiar contribution of Ricoeur consists in the emphasis on the active as well on the passive role of acknowledgment, by means of a way that takes in view all themarks of gift and his connotations of giving thanks, making clear, then, also the central position of receiving. The nerve of this flexible lattice is a certain "generosity of desire", that characterizes its festivity character in a ceremonial and symbolic way, which ends in the state of peace and ágape. So the concept of acknowledgement, as possible in a horizon of abundance and plenty, reveals itself as a founding relationship.